The Effect of Universal Free School Meals on Child BMI - Will Davis; Daniel Kreisman; Tareena Musaddiq (Institute of Labor Economics (IZA), 2023)
We estimate the effect of universal free school meal access through the Community Eligibility Program (CEP) on child BMI. Through the CEP, schools with high percentages of students qualified for free or reduced-priced meals can offer free breakfast and lunch to all students. With administrative data from a large school district in Georgia, we use student-level BMI measures from the FitnessGram to compare within-student outcomes before and after CEP implementation across eligible and non-eligible schools. We find one year of CEP exposure increased expected BMI percentile by about 0.085 standard deviations, equivalent to a nearly 1.88-pound weight increase for a student of average height. We also find that the program led to a small increase in the likelihood of overweight and limited evidence of a small decrease in the likelihood of underweight. We do not find that the program increased student obesity risk. Examining the effects of CEP on child BMI by grade suggests that the overall effect is largely driven by students in middle schools, highlighting potential heterogeneity in the program's impact across grades. The findings of this paper are relevant for researchers and policymakers concerned with the effects of universal free school meals on student health.
Keywords: I10; I28; 330; school meals; child BMI; community eligibility provision; free lunch